Cloning and expression of the major 47-kilodalton surface immunogen of Treponema pallidum in Escherichia coli. - Norgard, M V (1986)
Monoclonal antibodies directed against the 47-kilodalton (kDa) major outer membrane surface immunogen of virulent Treponema pallidum subsp. pallidum were used to select Escherichia coli recombinant clones expressing the 47-kDa immunogen. The phenotype of the clones was dependent on the presence of recombinant plasmid in the host cell. Southern hybridization revealed that the cloned T. pallidum subsp. pallidum DNA sequence was an accurate representation of the T. pallidum subsp. pallidum genomic DNA arrangement. Purified immunoglobulin G from rabbits experimentally infected with T. pallidum subsp. pallidum and human secondary syphilitic sera specifically reacted with the clones, while normal human serum or immunoglobulin G from normal rabbit serum did not. Results of Southern hybridization indicated that a homologous 47-kDa immunogen gene was absent in at least four species of nonpathogenic treponemes tested, as well as from total rabbit genomic DNA. Rabbit anti-T. phagedenis biotype Reiter (treponemal nonpathogen) antiserum and a monoclonal antibody directed against a common treponemal determinant were unreactive with the clones. Western blotting and radioimmunoprecipitation experiments with specific monoclonal antibodies revealed that the recombinant (E. coli) and native (T. pallidum subsp. pallidum) forms of the antigen had identical electrophoretic mobilities. The availability of recombinant 47-kDa immunogen provides a new opportunity for biochemical analysis of the protein, structure-function studies, examination of its role in microbial pathogenesis, and assessment of its diagnostic and vaccinogenic potentials.